A user-oriented model for global enterprise portal design. (6th May 2010) - Feng, X.; Ehrenhard, M.L.; Hicks, J.N.; Maathuis, S.J.; , Y. Hou
Enterprise portals collect and synthesise information from various systems to deliver personalised and highly relevant information to users. Enterprise portals' design and applications are widely discussed in the literature; however, the implications of portal design in a global networked environment have barely been explored. This paper aims to highlight the challenges of enterprise portals for international, transnational and multinational businesses, paying special attention to the influence of national culture on enterprise portal design. A user-oriented model for enterprise portal design is put forward emphasising the relevant cultural characteristics of the portal users influencing portal design. The incorporation of these characteristics to the portal design will support both portal contribution and portal benefits, ultimately leading to improved business processes.